The plastic-scape: Applying seascape ecology to marine plastic pollution - Murphy, Erin L.; Polidoro, Beth; Gerber, Leah R. (Frontiers in Marine Science, 2022)
Marine plastic pollution (MPP) has emerged as a global sustainability challenge with environmental, social, and economic consequences. This has inspired action at every scale of governance—from the local level to international institutions. However, policy and management efforts have been reactive and ad hoc, resulting in concerns about their efficacy, cost, and unintended consequences. To adequately address MPP and its global impacts, a systematic, evidence-based approach is needed. Seascape ecology, a subdiscipline of landscape ecology, is an interdisciplinary system science focused on the reciprocal relationship between the patterns and processes that shape seascapes. In this paper, we define the plastic-scape as all the social-ecological systems that interact with plastic (as a product and pollutant), the drivers and pathways of MPP, and the natural and human environments impacted by MPP. We then demonstrate the ways in which principles, methods, tools, and transdisciplinary research approaches from seascape ecology can be applied to better understand the plastic-scape, inform future MPP research and improve management strategies.